APPLICATION OF ENDORSMENT TO PRODUCT PROMOTION ACTIVITIES IN AN ISLAMIC ECONOMIC PERSPECTIVE - Fata, Zainol; Azam, Ilyas Nurul (J-Mabes: Jurnal Manajemen, Akuntansi, Bisnis dan Studi Ekonomi Syariah, 2024)
Nowadays, in the modern era, the use of marketing strategies aims to modify and introduce existing products to the wider community. Along with the times and accompanied by technological developments, the use of advertising as a promotional medium has changed. One way or steps that companies can take to create advertisements that are appropriate to the current era in marketing their products is by using endorsements. The goal to be achieved in this writing is how the social economy views the use of endorsements in promotional activities The research uses the approach used in this research, namely using a qualitative descriptive approach, while the type of research used in this research is literature. The results of this research are that endorsements are one type of muamalah that is not prohibited in Islam, but there is nothing prohibited in this activity in sharia provisions